PCR method application to assess the molecular markers of intestinal barrier integrity in farming broilers - S. A. Shatalov; M. Kirici (Theoretical and Applied Veterinary Medicine, 2025)
The maintenance of intestinal health in broiler chickens is one most critic task to take the farming profitability in post-antibiotic era. Feed additives contained the blend of fatty acids and glycerides are proposed as a promising alternative to growth promoters and antimicrobial tool. Present study carried out to assess the impact of short chain fatty acid contained monoglyceride blend (SCAFMB) on the modulation of intestinal immunity, pro- and anti-inflammatory balance, and microbiota community state. A total of 80.000 broilers (cross Cobb 500) were involved in the study and raised in two equal poultry houses. Control group of broilers fed with basal industrial farm diet. Exposed to SCAFMB chicken group fed with basal diets supplemented with 1 g/kg SCAFMB. The thin intestine tissue samples were collected at 14-th, 21-nd, and 28-th days of age. The level and ratio of interferon-α and interferon-γ were measured with western blot and PCR analysis. The modulation of microbiota community state was estimated through the Staphylococcus spp. and Enterococcus spp. content. Results have shown that SCAFMB supplemented group exhibited the reciprocal increase in interferon-α and decrease in interferon-γ content (P < 0.05) in compare with control group. These changes were similar on both 21-nd and 28-th day of life. Furthermore, SCAFMB feed additive application initiated the suppression of Staphylococcus spp. content in compare with control group (P < 0.05). Contrary, the content of Enterococcus spp. in thin intestine of SCAFMB-exposed group was higher than similar content in broiler fed with basal diet. Besides, the mortality indices were ameliorated by SCAFMB feed additive supplementation from 14-th to 28-th days of life. Thus, obtained results demonstrated beneficial effect of SCAFMB feed additive application in poultry farming in respect to intestinal health and broiler productivity. In conclusion, protective effect of SCAFMB can be related to regulatory feedback between intestinal immunity mechanisms and changes in microbiota community.